Parental involvement and M-learning adoption in distance higher education: Structural equation analysis - FALEBITA, Oluwanife Segun; TALASI, Tatalo; AREMU, Bamidele Victor; AMBODE, Akinbiyi Benard; OKUNADE, Adesina Isaac (Edelweiss Applied Science and Technology, 2026)
This work examined the utilization of mobile learning (m-learning) among distance learning undergraduates and the influence of parental involvement on its usage. The study is underpinned by the Technology Acceptance Model (TAM). It employed a descriptive survey research design that surveyed 676 distance learning students in Southwest Nigeria through an online questionnaire titled “Parental Involvement on M-learning Utilization Questionnaire.” Data were collected over eight weeks and analyzed using PLS-SEM in SmartPLS 4. The study revealed that attitudes towards m-learning significantly influence its use among distance-learning undergraduates. Additionally, perceived ease of use positively influences attitudes, perceived usefulness, and m-learning usage, while perceived usefulness influences m-learning usage but not attitudes. Also, it was found that parental involvement in communication enhances perceived ease of use and usefulness but does not influence attitudes. In addition, parental involvement in decision-making positively influences attitudes, perceived ease of use, and perceived usefulness, whereas involvement in home learning shows no significant influence on attitudes, perceived ease of use, or perceived usefulness of m-learning. This should encourage the stakeholders of tertiary institutions in Nigeria to embrace and utilize m-learning for a smooth academic calendar. Also, developers and educators need to consider user experience on m-learning platforms by simplifying interfaces, offering clear instructions, and guaranteeing technical assistance, which may improve students' perceptions and, ultimately, engagement levels.